The Invisible Hurdle: Hidden Costs for First-time, International, Graduate Students in the United States - Gray, Nigel (Journal of International Students, 2023)
International students pursuing higher education in the United States incur additional expenses compared to domestic students by spending on foreign credential evaluations and visa applications. These costs are usually not reflected in program fee structures, are non-refundable, and are not covered by financial aid, creating significant, and often unforeseen, financial strains on international students, particularly those from low-income backgrounds. This study compared the costs of two major foreign credential evaluators (Educational Credential Evaluators and World Education Services) and factored in the price of visa processing fees and the I-901 Student and Exchange Visitor Information System fee. It found that First-time, International, Graduate students pay up to $691 for foreign credential evaluations and visa applications. The paper suggests that higher education institutions should provide more transparent fee breakdowns and enhance financial aid packages to better support these students.